Atributos químicos e físicos do solo sob aplicação de vinhaça por anos consecutivos - Mundim, Daniel Alves (2016)
The use of vinasse in fertigation is common practice to industries producing sugar and alcohol and its proper distribution in the soil is responsible for improvements in the physical and chemical attributes of this natural resource, but the disorderly application can negatively influence and contribute to the impracticability of agricultural practices. Thus this study aimed to identify and analyze the changes in a red yellow podzolic soil dystrophic located in Cordanta J farm in the municipality of Conceição da Barra - ES where the practice of using vinasse has been going on for over 15 years, with the comparison to farm Cordanta P, area of sugarcane without fertigation, farm Aliança with eucalyptus area and native forest.Treatments were performed in a randomized design in a factorial 2 (Environment) x 4 (depth) with 04 repetitions where disturbed soil samples were taken and undisturbed in the depths of 0-20, 20-40 40-60 and 60-80 (cm).Soil samples were sent CEUNES soil physics laboratory where they were evaluated water retention curve characteristics on the ground, density, hydraulic conductivity. For Chemical analyzes deformed samples were sent to Fullin laboratory which analyzed the concentrations of macro and micro nutrients, organic matter and pH were also analyzed electrical conductivity (EC) and sodium absorption ratio (SAR). The results showed that the soil with native plants had higher water retention capacity while fertigated area showed lower capacity and also lower amount of water available (WA) and readily available water (RAW), there was a significant reduction in hydraulic conductivity in the fertirrigated environment in deeper layers indicating compression. The determination coefficient of adjustment of the water retention curves in soil is greater than 99% and adjustment parameters increased with depth. A significant increase in phosphorus-Mehlich nutrients (mg dm-3 ), potassium (mg dm-3 ), sulfur (mg dm-3 ), Zinc (mg dm-3 ) and sodium (mg dm-3 ) in fertigated area, pH and organic matter showed no significant difference between the environments. Sodium levels were significantly higher in the area of native forest, hence the SAR and EC values were higher at this location. Overall, there was an improvement in soil chemical properties in comparison to areas where there was no application of vinasse. Regarding to the physical soil characteristics, the significant reduction in hydraulic conductivity (KFS) appears to be associated with the accumulation of salts of potassium (K) that showed high content in this area and is also the main nutrient found in the composition of vinasse.